2014
DOI: 10.1186/1471-2407-14-594
|View full text |Cite
|
Sign up to set email alerts
|

The radiosensitising effect of gemcitabine and its main metabolite dFdU under low oxygen conditions is in vitro not dependent on functional HIF-1 protein

Abstract: BackgroundRegions within solid tumours often experience oxygen deprivation, which is associated with resistance to chemotherapy and irradiation. The aim of this study was to evaluate the radiosensitising effect of gemcitabine and its main metabolite dFdU under normoxia versus hypoxia and to determine whether hypoxia-inducible factor 1 (HIF-1) is involved in the radiosensitising mechanism.MethodsStable expression of dominant negative HIF-1α (dnHIF) in MDA-MB-231 breast cancer cells, that ablated endogenous HIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Therefore, we hypothesized that hypoxia might induce anti-EGFR therapeutic resistance. To test this hypothesis, we evaluated the cytotoxicity of the EGFR-blocking monoclonal antibody cetuximab and the small molecule EGFR tyrosine kinase inhibitor erlotinib in three HNSCC cell lines under hypoxic conditions for 24 and 72 h. We previously validated induction of HIF-1α and its downstream targets as well as induction of HIF activity in our experimental model [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypothesized that hypoxia might induce anti-EGFR therapeutic resistance. To test this hypothesis, we evaluated the cytotoxicity of the EGFR-blocking monoclonal antibody cetuximab and the small molecule EGFR tyrosine kinase inhibitor erlotinib in three HNSCC cell lines under hypoxic conditions for 24 and 72 h. We previously validated induction of HIF-1α and its downstream targets as well as induction of HIF activity in our experimental model [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic conditions (0% O 2 , 5% CO 2 , 95% N 2 ) were achieved in a Bactron IV anaerobic chamber (Shel Lab, Cornelius, OR, USA) and we used the hypoxia model previously optimized and characterized [ 21 , 22 ]. Measurements with ToxiRae II air oxymeter (Rae BeNeLux, Hoogstraten, Belgium) confirmed that the oxygen tension in the gas phase was stable at <0.1% O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In muscle invasive bladder cancer evidence from phase I/II trials supports the concurrent administration of gemcitabine and radiotherapy as a bladder preservation strategy [ 53 , 54 ]. In the breast cancer cell line MDA-MB-231, the SER for gemcitabine and radiation under hypoxia was 1.59 and under normoxia 1.70 [ 55 ]. The radiosensitizing effects of gemcitabine in breast cancer are greater than the effects reported in this study for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments can provide some information, but do not necessarily reflect the complex in vivo microenvironment. Some chemotherapy drugs used for LAUPC treatment apparently sensitize cell cultures to X-rays ( 17 , 18 ), but simple additive effects are observed when the drugs are given in vitro concomitantly to charged particles ( 19 , 20 ). Moreover, in many clinical protocols, chemotherapy is given as adjuvant or neo-adjuvant, and even when concomitant is often continued after the radiotherapy cycle.…”
Section: Methodsmentioning
confidence: 99%